Restoration: Implant with Devastated Platform through Metal Post - Luna Salinas Tatiana; Del Valle Lovato Juan (Hindawi Limited, 2017)
Case Presentation. Implant prostheses are a successful treatment for replacing missing teeth. However, this treatment modality can have biological and mechanical complications causing serious problems for the dentist, as demonstrated in this clinical case. The patient presented with a fractured screw and a severely damaged implant hex connection that corresponded to the second premolar, upper left, stating that she unsuccessfully tried to remove the prosthetic screw, which was most likely to have been loose. After clinical and radiographic review, it was decided to remove small fragments of the fractured prosthetic screw inside the implant head. Removal by conventional methods was unsuccessful but was eventually achieved through use of a bur. Then it was possible to make a cast post (gold-palladium) and develop a fixed prosthesis (silver-palladium), which were attached with luting cement. A cast post (gold-palladium) was made and a fixed prosthesis was developed (silver-palladium), which were attached with luting cement, the same ones that can present mechanical complications such as fractures between the third and fourth thread of the implant, loosening of the abutment, and/or the prosthetic screw in individual crowns, most frequently in partially edentulous patients, mainly in the premolar and molar regions of the maxilla. Conclusion. Therefore the present technique used in this case is very simple, noninvasive, and useful to readers.